Women, Culture and Postcolonial Feminism in Siti Kartini by L. Suma Tjoe - Ekaristi, Lidwina Putu Gratia; Sabrina, Renanda Putri; Dewojati, Cahyaningrum (International Journal of Multidisciplinary Sciences, 2025)
During the colonial period, bumiputera women were positioned at the lowest social strata viewed as unintelligent, powerless, and lacking value. The culture of oppression that prevailed at the time reduced these women, including those of noble lineage, to objects of service exchange among the socially inferior. This structural subjugation and marginalization are critically represented in L. Suma Tjoe Sing's novel Siti Kartini, which serves as the material object of this research. The primary objective of this study is to explore and narrate the forms of resistance shown by bumiputera female characters against colonial oppression within the novel. Utilizing the framework of postcolonial feminism, which examines the intersection of gender and colonial power structures, this study employs a qualitative descriptive method to analyze the text. The findings indicate that colonization inevitably leads to cultural contact and interaction between colonizers and the colonized, often resulting in the systemic oppression of the latter. Within this context, women become doubly marginalized—both as colonized subjects and as females prompting them to engage in various forms of resistance. The novel Siti Kartini illustrates that bumiputera women, despite being socially oppressed, possess the agency and determination to challenge colonial and patriarchal domination.